Pengaruh Brand Image, Online Customers Review, dan Gratis Ongkir Terhadap Keputusan Pembelian Pada E-Commerce Shoppe - Rahmania, Vanesha; Iqbal, Muhammad; Oktavianti, Santi; Ruhmana, Haryati (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2026)
This study investigates the effects of brand image, online customer reviews, and free shipping on purchase decisions among Shopee users, focusing on students of the Faculty of Economics at Universitas Sumatera Selatan. The rapid growth of e-commerce has intensified competition among digital marketplaces, encouraging platforms to strengthen their marketing strategies through brand building, customer-generated information, and promotional programs. In online purchasing contexts, consumers are unable to directly examine products, making brand perception and review information essential in reducing uncertainty, while free shipping is often considered an attractive incentive that can stimulate purchasing behavior.This research employed a quantitative descriptive approach using a structured questionnaire as the primary data collection instrument. The population consisted of active students who had made purchases on Shopee at least three times within the last six months. The sample size was determined using the Slovin formula with a 10% precision level, resulting in 82 respondents. Data were analyzed using multiple linear regression to examine both partial and simultaneous relationships between the independent variables and purchase decisions.The results show that brand image, online customer reviews, and free shipping each have a positive and statistically significant influence on purchase decisions. Furthermore, the simultaneous test confirms that the three variables jointly contribute significantly to purchase decisions. The coefficient of determination indicates that the proposed model explains 22.6% of the variance in purchase decisions, while the remaining proportion is influenced by other factors not included in this study. These findings highlight the importance of strengthening brand credibility, maintaining review quality and trustworthiness, and optimizing free shipping programs as strategic efforts to improve consumer purchasing decisions in e-commerce settings.